KINERJA PENYULUH PERTANIAN DI BEBERAPA KABUPATEN PROVINSI JAWA BARAT - Ani Leilani; Amri Jahi (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2006)
A research on the relationship of several selected characteristics of Agricultural Extension Agents and their performance had been conducted in July through September 2005. The Objectives of this study were: 1) to determine the distribution of Agricultural Extension Agents on several selected characteristics, 2) to identify the performance of Agricultural Extension Agents based on their official main duty, and 3) to determine the extent of relationships between the agricultural extension agents’ characteristics and their performance. One hundred Agricultural Extension Agent respondents were selected randomly to meet the objectives. The respondents were from Bogor, Sukabumi, Bekasi, Majalengka, and Subang districts. A closed end questionnaire was developed to gather needed data. The collected data were then analyzed descriptively. Kendall W Concordance procedure was used to determine the extents of relationship among agents’ characteristics and their perceived performance. The research results showed that: (1) some of the agents’ characteristics were correlated significantly with their performance, (2) the agents’ performance in accomplishing their official duties was mostly good, (3) the official duties that they considered as important was Extension Program Development, (4) while the ones that they considered as less important was professional development, evaluation, reporting their monthly duty, and preparing extension materials.